Weed Interference on the Accumulation of Dry Mass and Macronutrients of Eggplant ‘Nápoli’ - MARQUES,L.J.P. (2019)
ABSTRACT: The presence of weeds may affect both growth and nutrition of agricultural crops due to interference. The objective was to evaluate the interference of weeds in the dry mass distribution and in the accumulation of dry mass and macronutrients in eggplant. The treatments consisted of increasing weed-free and weedy periods (0-14, 0-28, 0-42, 0-56, 0-70, 0-84, 0-98, 0-112, 0-126, 0-140 and 0-154 days after transplanting) in eggplant ‘Nápoli’. The experiment was arranged in a randomized block design with three replicates. Weeds affected the distribution of dry mass between vegetative and reproductive organs of eggplant. There was a significant reduction in the accumulation of dry mass and macronutrients when weeds grew with eggplant crop beyond 42 days after transplanting, reaching the maximum reduction of 79%, 75%, 80%, 82%, 83%, 83% and 80% in the accumulation of dry mass, K, N, Ca, Mg, P and S, respectively. Therefore, the weed community significantly affects the growth and mineral nutrition of eggplant ‘Napoli’, and there should be no weed-crop coexistence beyond 28 days after seedling transplanting.